Effect of percoll density gradient centrifugation on semen quality of X- sperm enriched crossbred bull semen - Chaudhary, Deeksha; Sharma, Mridula; Devlal, Kamal (The Indian Journal of Animal Reproduction, 2023)
The present study was conducted to observe the effect of percoll density gradient centrifugation on quality of semen. Ejaculates were collected by AV method from Sahiwal bulls. X-sperm enrichment was done by percoll density gradient method i.e. 7 layers (70-10%). Centrifugation was done at 750 g (22-24°C) for 15 min. The pellets obtained were diluted in EYC medium. Semen quality was evaluated in fresh semen (Control), in pellet of normal centrifugation (Group I), supernatant of centrifugation in percoll density gradient (Group II) and pellet of centrifugation in percoll density gradient (Group III). To assess the quality of enriched semen pH, mass motility, progressive motility, live spermatozoa %, abnormal spermatozoa %, HOST % and intact acrosome % were evaluated. Number of progressively motile sperms in pellet of X-   enriched semen were non-significantly increased and significantly (P
Keywords: Percoll density gradient; Semen; X-enrichment; Qualitative assessment; Crossbred cattl